Implications of Psychological Pricing on Contemporary Muslim Retailers and Consumers in Nigeria - Sikiru Atanda Adenigba; Hassan Yoosuf Akorede (Journal of Islamic Economic and Business Research, 2023)
Pricing is one of the major components of businesses. Retailers have adopted different pricing modes due to the need to devise sustainable pricing strategies. This is one of the reasons for the development of psychological pricing. Psychological pricing has adverse effects on Muslim retailers and consumers due to their involvement in zulm (deception). Therefore, this study examined the implications of psychological pricing on Muslim retailers and consumers in Nigeria. The paper adopted qualitative and analytical methods. The qualitative method was used to review related literature, while the analytical method was used to examine and analyse the implications of psychological pricing. This study found that psychological pricing is used for profit maximization through deception. Psychological pricing has led to the involvement of Muslim retailers and consumers in vices such as deception, lying, and trickery. This paper concluded that psychological pricing affects the spiritual and moral lives of Muslim retailers and consumers. The paper recommended that Muslim retailers and consumers adopt and accept other pricing strategies that do not involve ambiguity and deception. They are also encouraged to use credit cards in order to avoid paying beyond the tagged price of a commodity.